International Regulatory Guiding Documents and Best Practice Recommendations on Peripheral Nervous System (PNS) Histopathologic Evaluation in Good Laboratory Practice (GLP)-Compliant Animal Toxicity Studies. (January 2020) - Bolon, Brad; Bradley, Alys; Butt, Mark T.; Jensen, Karl; Rao, Deepa B.
Assessment of the peripheral nervous system (PNS) tissues during animal toxicity studies generally is included within guiding documents issued by regulatory agencies of individual nations (eg, US Environmental Protection Agency, US Food and Drug Administration) and multinational federations (eg, European Medicines Agency) as well as international cooperative efforts (eg, International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use, Organisation for Economic Co-operation and Development). The present list of major regulatory guiding documents categorizes recommendations from around the world for sampling and processing PNS tissues (nerves and ganglia) for general animal toxicity studies (ie, where neurotoxicity is not expected) and specialized neurotoxicity studies (ie, where neurotoxicity is anticipated or known to occur). In general, regulatory guidelines call for collection of one or more sensorimotor nerves (usually the sciatic trunk and its branches), though details vary among agencies. Regulatory guiding documents represent a "starting point, " after which additional PNS samples and/or special methods may be implemented at the applicant's discretion. Best practice recommendations for PNS sampling and processing in animal toxicity studies endorsed by multiple global societies of toxicologic pathology encompass and expand on existing regulatory guidelines.